Una semántica ejecutable en lógica de reescritura para programación espacial concurrente por restricciones (SCCP) (2017)
This document presents an executable semantics in rewrite logic for Concurrent Spatial Constraint Programming, abbreviated SCCP. SCCP is a computational model used to reason about spatial information and knowledge distributed among the processes of a system. In SCCP, the processes simulate common knowledge statement and global information query, in turn, each agent in SCCP has its own information space, and epistemic entities such as knowledge or beliefs are represented in a system of parametric constraints. The executable semantics of SCCP is made available to users and programmers through a tool that integrates a programming language and specification into Maude. From this tool, in addition to simulating programs in this language, it is also possible to verify properties specified in temporal linear logic.